Integration of Information and Communication Technology in the Primary School Curriculum of Timor-Leste: A Systematic Review - Salvador Magno Ximenes (International Journal of Multidisciplinary Approach Research and Science, 2025)
The implementation of Information and Communication Technology (ICT) at every level in the 2014 Primary School Curriculum of Timor-Leste functions as the key driver for improving teaching quality while extending classroom reach. A comprehensive evaluation examines essential details, including benefits and limitations, that are developed as a result of the primary education implementing ICT. Research shows that information and communication technology lead to better engagement in learning, result in higher academic performance, and help fill educational gaps that affect distant and underprivileged areas. Digital tools help students discover engaging teaching strategies that strengthen their capacity for critical thinking and problem-solving. The implementation faces multiple barriers because of inadequate school facilities, and lack of teaching staff qualifications, and continuing digital divide challenges. Multiple issues affect rural education settings because many schools do not have internet access and appropriate technology equipment, and teachers are limited in their ability to use ICT effectively. The educational system in Timor-Leste needs to address major weaknesses before it can maximize the potential benefits from the implementation of ICT. The results support the need to create policies that promote inclusive and sustainable digital learning because students should have equal access to ICT.